2016
DOI: 10.1159/000452712
|View full text |Cite
|
Sign up to set email alerts
|

HIV Drug Resistance and Phylogeny Profile in Naïve and Antiretroviral-Experienced Patients in Tehran, Iran

Abstract: Background: Increasing the accessibility of antiretroviral therapy (ART) has caused the emergence of drug resistance in patients receiving ART and in naïve patients. The aim of this study was to evaluate HIV subtype and drug resistance between naïve patients and ART-experienced patients. Methods: Blood samples were collected from 78 antiretroviral and naïve HIV-1 patients; antiretroviral-resistant mutations and subtyping were then determined by sequencing pol regions. Results: Phylogenetic analysis revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 28 publications
1
5
2
Order By: Relevance
“…Although in previous studies, G190SA mutation accounted for the most frequent NNRTI mutations in Iran [12], we detected K103E/N mutation more frequently (34.2%). K103N is a non-polymorphic mutation, which is regarded as a valuable index in patients who are receiving NVP and EFV [14, 15] and has the potential to reduce NVP and EFV susceptibility by 50- and 20-fold, respectively.…”
Section: Discussioncontrasting
confidence: 90%
See 1 more Smart Citation
“…Although in previous studies, G190SA mutation accounted for the most frequent NNRTI mutations in Iran [12], we detected K103E/N mutation more frequently (34.2%). K103N is a non-polymorphic mutation, which is regarded as a valuable index in patients who are receiving NVP and EFV [14, 15] and has the potential to reduce NVP and EFV susceptibility by 50- and 20-fold, respectively.…”
Section: Discussioncontrasting
confidence: 90%
“…Individuals with M184V mutation are subjected to high resistance to FTC and 3TC, which are the common medications of each first-line regimen. M184I/V mutation was the most frequent mutation (31.6%) among NRTI-based regimens; similar findings were observed in studies from Iran [10, 12] and other regions in which the common mutation for NRTIs was M184V, with an estimated prevalence of 40 and 88.5%, respectively [13]. 3TC and FTC M184V mutation creates a significant decrease in viral replication capacity.…”
Section: Discussionsupporting
confidence: 80%
“…Our data were more similar to 2 other studies by Baesi et al [17,18] (in 2015) which found a frequency of 80 and 88% CRF 35_AD. In 2016, a third study by Baesi's group (Farrokhi et al [19] ) found the frequency of CRF35_AD to be 96.1%. These findings are also consistent with an earlier national pilot study by Mousavi et al [20] (in 2010) which found subtype CRF35_AD to be the most common in Iran.…”
Section: Discussionmentioning
confidence: 96%
“…The RT and protease genes were amplified using the following methods. For obtaining RT PCR product, 2 series of primer was used, introduced in last studies[16] [Table 1]. Nested PCR was done with inner primers of last studies with separate material of PCR belonging to Fermentas/Thermo Fisher Scientific Company.…”
Section: Methodsmentioning
confidence: 99%
“…Nested PCR was done with inner primers of last studies with separate material of PCR belonging to Fermentas/Thermo Fisher Scientific Company. [1617] Nested PCR products were visualized on a 1.5% agarose gel with Fermentase DNA stain dye. The PCR products were decontaminated by a gel purification kit Qiagen (QIAquick PCR Purification Kit) and sequenced on both genes was sequenced by Sanger method.…”
Section: Methodsmentioning
confidence: 99%